(untitled) (Педагогіка вищої та середньої школи, 2012)
У статті розглянуто питання актуальності проблеми інтегрованого навчання старшокласників на уроках фізики і російської літератури. Ключові слова: інтеграція, інтегровані уроки, інтегроване навчання, мі предметні зв’язки, активізація пізнавального інтересу. In the article the question of actuality of problem of the computer-integrated teaching of senior pupils is considered on the lessons of physics and Russian literature. Key words: integration, computer-integrated lessons, computer-integrated teaching, intersubject connections, activation of cognitive interest.